Financial Planning in the Hotel Business - Ostonov Ma‘ruf (Indonesian Journal of Innovation Studies, 2022)
The article describes the questions of financial planning at the enterprises of hotel business. We describe the specifics of the financial plans of enterprises of hotel business, types of planning of hotel services are disclosed. The effectiveness of financial planning in modern regional hotel business is analyzed. Keywords: financial planning, hospitality, efficiency of financial planning, the current financing plan, the operational financial plan.